RETRACTED ARTICLE: Dclk1, a tumor stem cell marker, regulates pro-survival signaling and self-renewal of intestinal tumor cells - Parthasarathy Chandrakesan; Jiannan Yao; Dongfeng Qu; Randal May; Nathaniel Weygant; Yang Ge; Naushad Ali; Sripathi M. Sureban; Modhi Gude; Kenneth Vega; Eddie Bannerman-Menson; Lijun Xia; et al. (Molecular Cancer)
Abstract Background More than 80% of intestinal neoplasia is associated with the adenomatous polyposis coli (APC) mutation. Doublecortin-like kinase 1 (Dclk1), a kinase protein, is overexpressed in colorectal cancer and specifically marks tumor stem cells (TSCs) that self-renew and increased the tumor progeny in ApcMin/+ mice. However, the role of Dclk1 expression and its contribution to regulating pro-survival signaling for tumor progression in Apc mutant cancer is poorly understood. Methods We analyzed DCLK1 and pro-survival signaling gene expression datasets of 329 specimens from TCGA Colon Adenocarcinoma Cancer Data. The network of DCLK1 and pro-survival signaling was analyzed utilizing the GeneMANIA database. We examined the expression levels of Dclk1 and other stem cell-associated markers, pro-survival signaling pathways, cell self-renewal in the isolated intestinal epithelial cells of ApcMin/+mice with high-grade dysplasia and adenocarcinoma. To determine the functional role of Dclk1 for tumor progression, we knocked down Dclk1 and determined the pro-survival signaling pathways and stemness. We used siRNA technology to gene silence pro-survival signaling in colon cancer cells in vitro. We utilized FACS, IHC, western blot, RT-PCR, and clonogenic (self-renewal) assays. Results We found a correlation between DCLK1 and pro-survival signaling expression. The expression of Dclk1 and stem cell-associated markers Lgr5, Bmi1, and Musashi1 were significantly higher in the intestinal epithelial cells of ApcMin/+mice than in wild-type controls. Intestinal epithelial cells of ApcMin/+mice showed increased expression of pro-survival signaling, pluripotency and self-renewal ability. Furthermore, the enteroids formed from the intestinal Dclk1+ cells of ApcMin/+mice display higher pluripotency and pro-survival signaling. Dclk1 knockdown in ApcMin/+ mice attenuates intestinal adenomas and adenocarcinoma, and decreases pro-survival signaling and self-renewal. Knocking down RELA and NOTCH1 pro-survival signaling and DCLK1 in HT29 and DLD1 colon cancer cells in vitro reduced the tumor cells’ ability to self-renew and survive. Conclusion Our results indicate that Dclk1 is essential in advancing intestinal tumorigenesis. Knocking down Dclk1 decreases tumor stemness and progression and is thus predicted to regulate pro-survival signaling and tumor cell pluripotency. This study provides a strong rationale to target Dclk1 as a treatment strategy for colorectal cancer.